RASIONALISASI PEMIKIRAN MAULANA MUHAMMAD ALI TERHADAP AYAT-AYAT MUKJIZAT PARA NABI DALAM AL-QUR’AN (Studi Analisis Terjemahan The Holy Qur’an Karya Maulana Muhammad Ali) - Herfina Herfina; Lukman Nul Hakim; Erika Septiana (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study seeks to explain the rationalization of Maulana Muhammad Ali's thoughts on supernatural miracle verses. He is of the view that the miraculous verses can be rational so that they can be accepted by reason in an effort to improve people's mindsets and make it easier to understand the verses of the Qur'an. By using the thematic method (maudhu'i) and the ulumul Qur'an approach in the form of I'jaz Qur'an, this research concludes that, Maulana Muhammad Ali said that the Qur'an is indeed rational, showing how the rationality of the Qur'an is. an understanding of the miracle verses in the rationality corridor. Maulana Muhammad Ali tries to dispel the impression that the verses about the miracles of the prophets that have been conveyed by the commentators as fantastic and fairy tales, Maulana Muhammad Ali views that the miracle is not an extraordinary event that has ever happened to prove the truth of a prophet. He understands miracle verses with rational liberal theology combined with understanding the verses of the Qur'an, science and references to the Bible. In conveying his opinion he provides scientific evidence for the truth of the Qur'an, the dominant factor influencing Maulana Muhammad Ali's thinking is the social environment factor.